Anxiety as a risk factor of Alzheimer's disease and vascular dementia. (28th November 2018) - Becker, Eva; Orellana Rios, Claudia Lorena; Lahmann, Claas; Rücker, Gerta; Bauer, Joachim; Boeker, Martin
Abstract : Background: The aetiology of dementia is not yet fully understood. Stress can have a damaging effect on brain health. The prognostic effect of anxiety is still unclear regarding Alzheimer's disease as well as vascular dementia. Aims: To explore the association between anxiety and future dementia. Method: Medline, PsycINFO, CINAHL, Web of Science and ALOIS were searched for publications up to 12 January 2018. Longitudinal studies with a follow-up of at least 2 years were included, if the trait or state anxiety had been assessed at baseline. Studies with cognitive impairment at baseline were not included. We used a random effects model to calculate the pooled time to Alzheimer's disease and incidence of vascular dementia. Results: Anxiety predicts risk of Alzheimer's disease ( n = 26 193 out of seven studies, hazard ratio1.53, 95% CI 1.16–2.01, P < 0.01) and vascular dementia ( n = 4916 out of two studies, odds ratio1.88, 95% CI 1.05–3.36, P < 0.01). The pooled hazard ratio regarding risk of Alzheimer's disease was still significant when excluding studies with critical risk of bias ( n = 14 110 out of six studies, hazard ratio 1.35, 95% CI 1.08–1.70, P < 0.01). Conclusions: Anxiety is a risk factor for both types of dementia. The temporal and functional relation between anxiety and dementia needs investigation in future studies. The protective value of treating anxiety should be explored further. Declaration of interest: None.